2019
DOI: 10.1186/s12889-019-6585-8
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic factors, body mass index and bariatric surgery: a Swedish nationwide cohort study

Abstract: Background: Bariatric surgery is considered to be the most effective method of weight loss today. The aim of the present Swedish study, which was performed in a country that has universal health care, was to investigate if there is an association between socioeconomic factors and bariatric surgery by taking body mass index (BMI) into account. Methods: In this prospective cohort study, BMI data were collected for the period 1985-2010 from the Military Service Conscription Register (for men) and from the Medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
1
7
1
1
Order By: Relevance
“…This study demonstrates, however, that sociodemographic inequalities associated with uncomplicated cystitis in women exist. This has also previously been shown in other recent studies in Sweden that have demonstrated associations between socioeconomic status, country of birth and geographic region with risks of negative outcomes of various medical conditions [31] , [32] , [33] , although these findings are not consistent [34] .…”
Section: Discussionsupporting
confidence: 59%
“…This study demonstrates, however, that sociodemographic inequalities associated with uncomplicated cystitis in women exist. This has also previously been shown in other recent studies in Sweden that have demonstrated associations between socioeconomic status, country of birth and geographic region with risks of negative outcomes of various medical conditions [31] , [32] , [33] , although these findings are not consistent [34] .…”
Section: Discussionsupporting
confidence: 59%
“…We did not identify an association between bariatric surgery and SES, which may imply that within the Swedish healthcare system, bariatric surgery is equally available for everyone who fulfills the surgical criteria, as suggested by a previous study [32]. In the present study, individuals with a nonNordic origin were slightly more likely to undergo bariatric surgery, which may be related to hereditary factors.…”
Section: Discussioncontrasting
confidence: 57%
“…Although severe and complex obesity is equally common among men and women in Sweden [ 14 ], the majority (75%) of those who undergo bariatric surgery in Sweden are women [ 14 – 17 ]. According to a global report from 51 countries the proportion of female patients undergoing bariatric surgery 2014–2018 was 73.7% [ 18 ].…”
Section: Introductionmentioning
confidence: 99%